Ta'tsir Kafa'ah An-Nahw Ala Hifd Al-Qur'an Li Talibat Hifd Al-Qur'an Fi Al-Ma'had Walisongo Cukir Jombang - Umami, Novita Rohmatul; Ghofur, Abdul (LPPM Universitas KH.A. Wahab Hasbullah, 2025)
This research was conducted to determine students’ knowledge of nahwu and their ability to memorize the Qur'an, as well as the influence of nahwu mastery on memorization ability at Madrasah Hifdzil Qur’an PPP Walisongo Cukir Jombang. The study is based on the essential role of nahwu, a core linguistic discipline, in learning and understanding Arabic—the primary language of the Qur’an. A mixed-methods approach (qualitative and quantitative) was used, employing Pearson correlation analysis and simple linear regression. Data were collected through interviews, nahwu comprehension tests, and memorization evaluations. Sampling was done purposively, involving 25 respondents from both college-level and TM-level students. The study found that most students had a fairly good understanding of nahwu, with an average score of 79.40. Their Qur’an memorization ability was also considered good, with an average score of 77.56. Statistical analysis showed a significant positive relationship between nahwu mastery and memorization ability, indicated by a significance value of 0.002 (< 0.05). This means that the higher the students’ nahwu mastery, the better their ability to memorize the Qur’an. These findings emphasize the importance of integrating linguistic competence, especially Arabic grammar, into Qur’anic memorization programs. The results offer meaningful contributions to Islamic education, particularly in pesantren, where such integration can improve the quality of tahfidz programs. It is expected that this research will serve as a useful reference for educators and pesantren administrators in designing more integrative curricula that align nahwu instruction with tahfidz, thereby enhancing students’ mastery of the Qur’an both structurally and spiritually.